الحرفيـــة والتصــرف في ترجمــة أدب الأطفــــال (مجلة الواحات للبحوث والدراسات, 2017)
Children’s Literature Had Long Been A Neglected Field Of Study, But Recently, There Has Been A Growing Interest In Studying And Translating This Literary Genre. Some Of The Books Written For Children Are Now Considered As Classics (Such As Pinocchio, Heidi, Harry Potter...Etc.), Have Been Translated Into Many Languages And Have Attracted Both Young And Adult Readers. This Growing Interest In Translating Children’s Literature Is Explained By The Need To Read The Literature Destined To Children In Other Countries And Cultures. Yet The Translation Of This Literary Genre Is Faced By Various Linguistic And Cultural Peculiarities That Differ From A Society To Another. This Study Will Attempt To Shed Light On The Definition Of Children’s Literature As Well As The Characteristics Of Its Translation From The Standpoint Of Some Translation Theories, By Analyzing Some Examples Taken From The Translation Of “Saharjibr Mahmoud” Of The “Harry Potter And The Philosopher’s Stone” Novel Into Arabic. Key Words -  Children’s Literature, Translation, Culture, Translation Theories, Literality, Adaptation.